Theoretical Analysis of the Effectiveness of the Sharia Financial System in Facing the Global Economic Crisis - Trisna Eka Sari; Melisa; Seri Wahyuni; Zulfikar Hasan (Penerbit Hellow Pustaka, 2024)
This research theoretically examines the effectiveness of the Islamic financial system in dealing with the global economic crisis. This study discusses economic theory, principles, characteristics, influence, comparison, experience, innovation and challenges in the Islamic financial system. Through a qualitative approach by conducting theoretical analysis of literature related to the Islamic financial system and the global economic crisis. The results of this research show that the Islamic financial system has great potential to become an attractive option in facing global economic challenges. By strengthening the foundation of sharia principles, developing appropriate innovations, and overcoming existing challenges, the sharia financial system can continue to develop and make a significant contribution to global financial stability and inclusion. This research confirms that the Islamic financial system, with its basic principles such as the prohibition against usury and excessive speculation, as well as the emphasis on real asset-based transactions, offers a more stable and fair alternative compared to the conventional financial system. The profit sharing principle shows the ability to reduce systemic risk by distributing risk more fairly among the parties involved in financial transactions.